Citric acid‐enhanced dissolution of polyphenols during soaking of different teas. Issue 12 (10th September 2019) - Li, Wenfeng; Zhang, Jing; Tan, Si; Zheng, Qiaoran; Zhao, Xin; Gao, Xiaoxv; Lu, Yalong
Abstract: This study examined the dissolution kinetics and antioxidant activity of tea polyphenols during the soaking of white, yellow, green, oolong, black, and dark teas. All these teas were, respectively, soaked with either freshly boiled distilled water (DW) or 10 mmol/L citric acid–water solution. The residue obtained from one extraction was used for the next extraction and this process was performed consecutively 10 times, soaking for 30 s each time. UHPLC‐QqQ‐MS measurement identified epigallocatechin gallate as the major polyphenol in white, yellow, green, oolong, and black tea infusions. As soaking times increased, the polyphenol concentrations rose initially and then dropped. Antioxidant activity was noted to decrease as soaking times increased in all tea infusions except for the DW‐soaked oolong and dark teas. These findings suggested that citric acid could increase the polyphenol content in tea infusions. Specifically, the cumulative contents of epigallocatechin gallate was noted to increase 2.1–5.1 times. Practical applications: After water, tea is one of the most consumed beverages in the world. Drinking tea has been linked to the reduced risk of various diseases, including cancer, cardiovascular system disease, obesity, and neurodegenerative diseases, largely due to its rich polyphenol content. Moreover, the addition of citrus to a tea infusion provides an interesting and feasible method for increasing the dissolution of tea polyphenols, a finding that offers extensive potential for applications in the development of compound tea drinks.